The mold cost estimation calculator for plastic injection mold manufacturing - Kamalrudin, massila; Mohan, Sharmini; Liew , Pay Jun; Abdullah, Rosmiza (2008)
This paper presents a research about the software system to calculate cost estimation in plastic injection mould manufacturing which is named as mold cost estimation calculator (MCEC). The objectives for MCEC is to optimize the cost estimation problems in plastic injection mould, assists industrial practitioner in estimating budget for manufacturing and assists for teaching purposes. There are three target users for this project that is industrial practitioner, lecturers and students. MCEC is developed using JavaScript programming language which each embedding of JavaScript within a particular environment provides the means to interact with that environment. All users may use this software easily even those who are not expert in injection molding because this software are user friendly.